Microbial community composition but not diversity changes along succession in arctic sand dunes - Poosakkannu, Anbu; Nissinen, Riitta; Männistö, Minna; Kytöviita, Minna-Maarit (Environmental Microbiology, 2017)
The generality of increasing diversity of fungi and bacteria across arctic sand dune succession was tested. Microbial communities were examined by high-throughput sequencing of 16S rRNA genes (bacteria) and internal transcribed spacer (ITS) regions (fungi). We studied four microbial compartments (inside leaf, inside root, rhizosphere and bulk soil) and characterized microbes associated with a single plant species (Deschampsia flexuosa) across two sand dune successional stages (early and late). Bacterial richness increased across succession in bulk soil and leaf endosphere. In contrast, soil fungal richness remained constant while root endosphere fungal richness increased across succession. There was, however, no significant difference in Shannon diversity indices between early and late successional stage in any compartment. There was a significant difference in the composition of microbial communities between early and late successional stage in all compartments, although the major microbial OTUs were shared between early and late successional stage. Co-occurrence network analysis revealed successional stage-specific microbial groups. There were more co-occurring modules in early successional stage than in late stage. Altogether, these results emphasize that succession strongly affects distribution of microbial species, but not microbial diversity in arctic sand dune ecosystem and that fungi and bacteria may not follow the same successional trajectories. peerReviewed